2001
DOI: 10.1139/cjfas-58-5-923
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic turnover in aquatic predators: quantifying the exploitation of migratory prey

Abstract: In the tidal freshwaters of Virginia, U.S.A., the blue catfish (Ictalurus furcatus), an introduced piscivore, derives a significant proportion of its nutrition from spawning anadromous fish (genus Alosa, including blueback herring (A. aestivalis), American shad (A. sapidissima), and alewife (A. pseudoharengus)). Because the Alosa are not continually available to I. furcatus, there is an isotopic turnover, defined as change in isotope composition due to growth and metabolic tissue replacement, in I. furcatus ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 17 publications
2
82
2
4
Order By: Relevance
“…This strong influence of growth on isotopic turnover has also been reported for ectothermic animals more generally (e.g. MacAvoy et al, 2001;Perga & Gerdeaux, 2005;Heady & Moore, 2013) and is attributed to them having lower metabolic activities than endotherms (Bosley et al, 2002;Tominaga et al, 2003). Indeed, Perga and Gerdeaux (2005) suggested that as fish, and other ectotherms, have a discontinuous pattern of growth over the year, the stable isotope values of their muscle might only reflect their food consumed during periods of growth.…”
Section: Discussionmentioning
confidence: 52%
“…This strong influence of growth on isotopic turnover has also been reported for ectothermic animals more generally (e.g. MacAvoy et al, 2001;Perga & Gerdeaux, 2005;Heady & Moore, 2013) and is attributed to them having lower metabolic activities than endotherms (Bosley et al, 2002;Tominaga et al, 2003). Indeed, Perga and Gerdeaux (2005) suggested that as fish, and other ectotherms, have a discontinuous pattern of growth over the year, the stable isotope values of their muscle might only reflect their food consumed during periods of growth.…”
Section: Discussionmentioning
confidence: 52%
“…λ can be defined as the sum of tissue net growth (k gt ) and tissue catabolic turnover (k dt ); thus, λ=k gt +k dt . If an animal, and hence, its tissues, is growing exponentially, then one can measure growth and determine the contribution of growth and tissue catabolic turnover to λ (Hesslein et al 1993;MacAvoy et al 2001;Jardine et al 2004;Sakano et al 2005;Suzuki et al 2005;Guelinckx et al 2007;Vollaire et al 2007;Zuanon et al 2007;Reich et al 2008). Following Reich et al (2008), we assumed that the fractional growth rate of a tissue was equal to the fractional rate of growth of the whole animal (k g ).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Thus, the use of carbon ( 13 C) and nitrogen ( 15 N) stable isotopes have become commonplace in dietary reconstruction for fishes. Few investigations, however, have determined turnover rates and tissue-diet discrimination factors (ΔX=δX tissue − δX diet ) of fish tissues in the laboratory before gathering animals and tissues from nature (Hesslein et al 1993;MacAvoy et al 2001;Jardine et al 2004;Sakano et al 2005;Suzuki et al 2005;Guelinckx et al 2007;Vollaire et al 2007;Zuanon et al 2007). These investigations suggest that empirically determined turnover rates and tissue-diet discrimination factors are essential for interpreting field isotopic signatures in a range of species.…”
Section: Introductionmentioning
confidence: 99%
“…Most laboratory diet-switch experiments (Hesslein et al 1993;Herzka and Holt 2000;MacAvoy et al 2001;Bosley et al 2002;Tominaga et al 2003) and field studies (Vander Zanden et al 1998;Maruyama et al 2001) show that growth is the primary factor causing stable isotopic change in fish following a diet shift. One field study of larval red drum has found significant metabolic turnover, and the authors suggest that differences between larval energetic requirements in the laboratory and in the field may account for variation between lab and field results (Herzka et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes have been used to determine the placement of mummichogs in food webs (Deegan and Garritt 1997) and estimate habitat use (Currin et al 2003). Knowledge of species-specific and tissuespecific turnover and nitrogen discrimination is important for accurate interpretation of isotopic data because past studies have demonstrated variation between species (Hesslein et al 1993;Herzka and Holt 2000;MacAvoy et al 2001;Bosley et al 2002) and also between tissues of the same species (Tieszen et al 1983;Hobson and Clark 1992).…”
Section: Introductionmentioning
confidence: 99%